High-power and high-beam-quality with unstable resonator in a Yb:YAG slab laser. - Jian Lei; Wei Jiang; Ruihan Dong; Gaozinan Yang; Jie Li; Xueshuang Deng (PLoS ONE)
The development and implementation of an unstable resonator laser system were explored in the present study, employing dual-end pumping of a Yb:YAG slab laser via laser diode (LD) arrays. The proposed system exhibited significant improvements in both power output and beam quality. The experimental design and execution of the laser oscillator were conducted under controlled conductive cooling conditions. Operating at a current of 90 A, the system achieved a total output power of 3823 W, with continuous-wave laser emission at 1030 nm observed bidirectionally. The measured beam qualities were 1.737 and 2.085, indicating that the system maintained good beam quality while achieving high power output. Additionally, an investigation into the optical-to-optical conversion efficiency was conducted, yielding a value of 35%. The findings underscore the exceptional performance of the devised unstable resonator within Yb:YAG slab lasers, with anticipated pivotal contributions to the broader laser domain. Novel approaches towards attaining high power output and superior beam quality laser sources were introduced, marking substantial advancements in Yb:YAG slab laser technology. The implications of these findings extend beyond the realm of laser technology, providing valuable insights applicable to a diverse range of optical, thus allowing the study's impact to transcend its immediate field.